INVESTIGATION ON THE ATTITUDE OF MATHEMATICS EDUCATION STUDENTS TOWARDS LEARNING MATHEMATICS IN GUILIN - Zhou Ying; Tommy Tanu Wijaya; Gao Ya (FKIP Universitas Muhammadiyah Prof. DR. HAMKA, 2020)
The aim of this study is to know attitude of mathematics education students towards mathematics learning in Guilin, China. The method used in this study is a qualitative method. The sample is taken using cluster random sampling from third and fifth semester students at Guangxi Normal University. Data were collected using questionnaire. The results of the research show that 27 male and 133 female students have a very good attitude towards mathematics. While, there are 4 male and 12 female students have a good attitude towards mathematics and 17 male and 5 female students have an average attitude towards mathematics. For the 5th semester students, there are 21 male and 151 female students with a very good attitude towards mathematics. On the other hand, there are 4 male and 18 female students that have a good attitude toward mathematics and 3 male and 7 female students have an average attitude towards mathematics.